The Deeper the Love, the Deeper the Hate - Jin, Wang; Xiang, Yanhui; Lei, Mo (Frontiers in Psychology, 2017)
Love and hate are basic human affects. Previous research has focused on the classification, functions, and other aspects of these two affects. However, few studies have been conducted on the relationship between love and hate. The present study investigated whether similarity within romantic partners was associated with greater feelings of love in the absence of betrayal, and greater hate in the presence of betrayal by using vignettes to induce love and hate in a sample of 59 young adults. The results showed that people who shared similar values and interests with the target persons were more likely to experience stronger love. Additionally, stronger feelings of love were associated with greater hate after the relationship was broken, suggesting a link between romantic love and hate. Our study revealed a complex picture of love and hate. People have different emotional reactions toward different target persons in the context of romantic love and hate. If one loves someone deeply and sometimes hates that person, the feeling of love may still be dominant in the context of betrayal. However, if one does not love that person, hate will be a much stronger feeling than love.